Teachers’ Continuous Professional Development in South Asia Challenges and Policy Initiatives - GV, Subitha (JOURNAL OF INDIAN EDUCATION, 2023)
The article is a review of teachers’ continuous professional development programmes in South Asia. The article, through a review of global reports, policy documents, and research articles argues for providing high quality teacher professional development programmes so as to improve the quality of school education in the South Asian region. With particular focus on countries such as India, Bangladesh, Sri Lanka, Nepal and Pakistan, this article analyses the current nature of professional development programmes for teachers, highlights policy thrusts and interventions in the area and suggests areas of improvement.